Prevalence of metabolic syndrome in patients with premature coronary artery disease proven by coronary angiogram - Sundaramoorthy, Varun; Mambatta, Anith Kumar; Chidambaram, Yoganathan; Gopalan, Rajendiran; Menon, Sujaya (International Journal of Research in Medical Sciences, 2017)
Background: Metabolic syndrome (MS) is associated with premature coronary artery disease (CAD). The aim of this study was to evaluate the prevalence of MS and its association with severity of CAD proven by coronary angiogram (CAG) in young patients. Methods: We included patients, aged 45 years or less, admitted with acute coronary syndrome (ACS), who had CAD confirmed by coronary angiography. They were divided into two groups according to the presence or absence of MS based on International Diabetes Federation (IDF) criteria. CAD was classified into single, double and triple vessel disease (TVD). The prevalence of MS and its individual parameters was calculated. Results: Among 90 young patients who presented with ACS, MS was present in 67 patients (74.44%). Among those with MS, the prevalence of each individual criterion was statistically significant in MS group (P <0.05). Prevalence of pre-existing hypertension and diabetes was significantly higher in MS group (p <0.01). Smoking, alcohol consumption and family history of CAD were not statistically significant in patients with and without MS. Fifteen out of 90 patients (14 in MS group) who presented with ACS had TVD in CAG, but this was not statistically significant (p 0.06). Conclusions: This study confirms a very high prevalence of MS in young Indian patients with premature CAD. MS was more prevalent than the conventional risk factor smoking in young CAD patients. We could not find significant difference in severity of CAD based on CAG between MS and non-MS group.